The Impact of Information and Communication Technology on the Technical Quality of Health Services "A Study at Al-Shatrah General Hospital #x2013; Dhi- Qar, Iraq" (Global Journal of Management and Business Research, 2020)
The aim of this study was to reveal the impact of information and communications technology in improving the technical quality of health services provided at Al-Shatrah General Hospital. The study sample was the type of intention sample. As the questionnaire was adopted as a tool to measure the variables of the study, it was distributed electronically to 108 doctors working in the hospital and the number of respondents was 93 doctors. Data were collected by the Excel program, while statistical analyzes were performed using the SPSS version 23 program. This study is the first of its kind in the Iraqi health sector.
Keywords: ICT; technical quality; health services; reliability; the safety